THE INFLUENCE OF LEADERSHIP STYLE, REWARD AND PUNISHMENT ON EMPLOYEE PERFORMANCE AT STARBUCKS COFFEE COMPANY DISTRICT 31 BANDUNG AREA - R. Rheina Amalina Iskandar; Yoyo Sudaryo; Andre Suryaningprang; Mochammad Mukti Ali; Erna Herlinawati; Dadan Abdul Aziz (Jurnal Scientia, 2023)
The purpose of this study was to analyze the relationship between Leadership Style, Reward, and Punishment on Employee Performance at Starbucks Coffee Company District 31 Bandung Area. In this study, the sample was employees at Starbucks Coffee Company District 31 Bandung Area with a total sample of 50 people. This study uses quantitative methods with probability sampling technique (saturated sample), and data analysis tools using SPSS version 25.0 program. Based on the results of research at Starbucks Coffee Company District 31 Bandung Area, shows that Leadership Style has a significant positive effect on Employee Performance, Reward also has a significant positive effect on Employee Performance and Punishment has a significant positive effect on Employee Performance, such as Leadership Style, Reward and Punishment Together.